2009 International Conference on Advances in Social Network Analysis and Mining 2009
DOI: 10.1109/asonam.2009.67
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Representation and Visualisation of the Dynamics in Computer-mediated Social Networks

Abstract: In this paper we will demonstrate the potential of processing and visualising the dynamics of computermediated communities by means of Social Network Analysis. According to the fact that computer-mediated community systems are manifested also as structured data, we use data structures like e-mail, discussion boards, and bibliography sources for an automatic transformation into social network data formats. Currently our developed converter DMD (Data Multiplexer Demultiplexer) supports GraphML, UCINET, and Pajek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Using Malzahn et al's (2005) algorithm, Harrer et al (2007) demonstrated additional links of interests between two teams in a scientific community mediated by the knowledge maps. Harrer et al (2009) further proposed a schema for multi-mode network transformations and presented a multi-mode network visualization to show temporal changes. In summary, since CSCL usually involves diverse types of entities and relations can develop in various ways, it is necessary to further use multi-mode network analyses to capture relations between entities and the mediating effects (Cela et al, 2015;Dado & Bodemer, 2017;Ouyang & Scharber, 2017).…”
Section: Basic Rationale Of Using Sna In Csclmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Malzahn et al's (2005) algorithm, Harrer et al (2007) demonstrated additional links of interests between two teams in a scientific community mediated by the knowledge maps. Harrer et al (2009) further proposed a schema for multi-mode network transformations and presented a multi-mode network visualization to show temporal changes. In summary, since CSCL usually involves diverse types of entities and relations can develop in various ways, it is necessary to further use multi-mode network analyses to capture relations between entities and the mediating effects (Cela et al, 2015;Dado & Bodemer, 2017;Ouyang & Scharber, 2017).…”
Section: Basic Rationale Of Using Sna In Csclmentioning
confidence: 99%
“…(2007) demonstrated additional links of interests between two teams in a scientific community mediated by the knowledge maps. Harrer et al. (2009) further proposed a schema for multi-mode network transformations and presented a multi-mode network visualization to show temporal changes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the analysis, the link structures of the Wikipedia article on schizophrenia and related articles that represented various explanatory approaches (social, biological, and psychoanalytical) were analyzed in a series of six annual cross-sectional snapshots for the years 2003-2008. The Weaver software (Harrer et al 2007) was then used to calculate SNA traits, such as centrality and density, for all of the Wikipedia pages that were linked at that time to these articles. Furthermore, SNA also allowed for the calculation of scores of the individual contributors with regard to the closeness or distance of their linking activities to the nodes that represented different views on the causes of schizophrenia.…”
Section: Examplementioning
confidence: 99%
“…In the context of collaborative online discussions, some students learn by actively evaluating other students' work, providing constructive commentaries and exchanging meaningful resources; other students learn by passive engagement, as well as viewing other students' posts and attached materials (Kim, Yoon, Jo, & Branch, 2018;Wise & Hsiao, 2019). Different levels of students' engagement in the online discourses enable some students to play distinct roles in the collaborative learning community (Harrer, Zeini, & Ziebarth, 2009;Kelly, Davis, Nelson, & Mendoza, 2008;Xie et al, 2018). Given that a discussion forum is a social space, a learning leader can be any student who exerts substantial influence on his or her peers during critical conversations that occur in the discussion forum.…”
Section: Introductionmentioning
confidence: 99%